2006
DOI: 10.2165/00023210-200620080-00005
|View full text |Cite
|
Sign up to set email alerts
|

Discontinuation Syndrome Associated with Paroxetine in Depressed Patients

Abstract: The discontinuation syndrome in patients taking paroxetine was more likely to occur in those patients who stopped taking the drug abruptly. The occurrence of the discontinuation syndrome was also correlated with younger age, but this association seemed to be secondary to the fact that younger patients tended to be more likely to abruptly stop taking the medication. It appears that the discontinuation syndrome can be prevented by carefully tapering the dosage of paroxetine when treatment is withdrawn. Interesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Himei and Okamura [54] investigated the occurrence of discontinuation symptoms by using clinical records of 385 outpatients who were diagnosed with a single episode of MDD and had undergone monotherapy with paroxetine in the previous 5 years. Findings showed that 10% of patients experienced discontinuation symptoms.…”
Section: Resultsmentioning
confidence: 99%
“…Himei and Okamura [54] investigated the occurrence of discontinuation symptoms by using clinical records of 385 outpatients who were diagnosed with a single episode of MDD and had undergone monotherapy with paroxetine in the previous 5 years. Findings showed that 10% of patients experienced discontinuation symptoms.…”
Section: Resultsmentioning
confidence: 99%
“…These results may indicate that the presence of comorbidity increased the probability to be treated earlier. We know from previous surveys that ED are frequently comorbid with Major Depressive Disorder, Anxiety Disorders and Substance or Alcohol Abuse [49] and also that ED relapses and successive hospitalizations reduce the response to treatment of comorbidity [50,51]. We may conclude that the comorbidity of severe ED psychopathology with other psychiatric disorders contributed to chronicity of illness and should be considered as a prognostic factor influencing long-term outcomes of rehabilitation programs and increasing financial dependence on society [52-54].…”
Section: Discussionmentioning
confidence: 99%
“… 3 Patients who experienced worse adverse symptoms when commencing antidepressant treatment were more likely to suffer withdrawal symptoms; therefore, identifying these people could allow closer monitoring during withdrawal. 10 …”
Section: Alleviating Antidepressant Withdrawal Symptomsmentioning
confidence: 99%